Moving through the Violence: Yemeni Migrants and the Reconstruction of Lifeworlds in Cairo - Hearn, Jonathan (AUC Knowledge Fountain, 2024)
This Master’s thesis is based on an ethnographic study, following the lives of a small number of Yemeni people rebuilding their lives in Cairo. Their displacement is the consequence of many factors not least the outbreak of war in 2014. In response to this, I ask: In the midst of ongoing conflict, how do Yemeni migrants go about reconstructing their lifeworlds in Cairo? That is, to ask how are Yemeni migrants in Cairo responding to the violent disruption of their social realities and what sense are they making of the consequences. The reorganisation of social realities disrupted by conflict means that Yemenis are adapting their habits and the mundane aspects of life to new surroundings and according to ever-changing possibilities. Attention to the minutiae of life reveals the relations between Yemenis and a range of actors imposing themselves in their social and political lives. I describe how Yemen’s social structures continue to exert considerable influence on Yemeni lives in Cairo. Furthermore, Yemeni institutions like schools and weddings are being reconstructed and reanimated from afar to ensure that Yemen continues for those who have been forced to leave. However, as Yemeni people in Cairo come to terms with the consequences of years of conflict, they must also address what the conflict means for those identifications they hold most dear. This thesis reveals the uncertainty of nationalist narratives of unity and the problematic legacy of certain nationalist symbols. For young Yemeni men and women, dealing with ambiguity and liminality of life in Cairo takes place alongside the fight for greater representation and the power to determine their place in whatever form Yemen’s future social reality takes.